Pemberian POC Urine Kambing dan Jarak Tanam terhadap Respon Pertumbuhan dan Hasil Tanaman Gambas (Luffa acutangula) - Lala Putri Ananda; Muhammad Idris (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the effect of giving goat urine POC and spacing on the growth response and yield of the luffa plant (Luffa acutangula). The method used was factorial RAK on two treatment factors (planting distance and giving POC goat urine) with three replications. Parameters observed were plant height, number of leaves, number of flowers, number of fruit and fresh fruit weight. The results showed that setting spacing significantly affected all parameters used, with the best spacing being: J2 = 40x50 cm. Administration of goat urine POC did not significantly affect the parameter of fresh fruit weight (ounces), but the best level of giving goat urine POC was U4 = 60 ml/L. As for the interaction between plant spacing and administration of goat urine POC, it has no significant effect on one parameter, namely fresh fruit weight. In conclusion, setting spacing is the most effective way to increase production and profits for gambas farmers. Keywords: Gambas, Planting distance, Goat Urine POC